2021
DOI: 10.1111/jcpt.13527
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dexmedetomidine on renal function after surgery: A systematic review and meta‐analysis

Abstract: What is known and objective: Acute kidney injury (AKI) is a complication following surgery and has been associated with worsened patient outcomes. Providers have used agents that may confer a degree of renal protection in the perioperative stage.Such is the case of dexmedetomidine, a selective alpha-2 adrenergic agonist used in the intensive care unit (ICU) as a sedative agent. The primary objective of this metaanalysis was to characterize the use of dexmedetomidine and to evaluate its impact on renal markers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…Dex did not significantly alter serum phosphorus, calcium, and uric acid, those electrolyte and renal function indexes we have tested all indicate that there was no substantive lesion in the renal parenchyma except serum sodium fluctuated within clinical normal ranges, for example, the normal ranges of BUN in male mice are 2.8–13.3 mmol/L ( Boehm et al, 2007 ). In addition, the decrease in serum CRE concentration indicates an increase in the creatinine clearance rate to a certain extent, which is consistent with previous research results ( Loomba et al, 2022 ). However, the above changes in renal function indicators suggest that Dex did not cause substantial damage to renal function.…”
Section: Discussionsupporting
confidence: 92%
“…Dex did not significantly alter serum phosphorus, calcium, and uric acid, those electrolyte and renal function indexes we have tested all indicate that there was no substantive lesion in the renal parenchyma except serum sodium fluctuated within clinical normal ranges, for example, the normal ranges of BUN in male mice are 2.8–13.3 mmol/L ( Boehm et al, 2007 ). In addition, the decrease in serum CRE concentration indicates an increase in the creatinine clearance rate to a certain extent, which is consistent with previous research results ( Loomba et al, 2022 ). However, the above changes in renal function indicators suggest that Dex did not cause substantial damage to renal function.…”
Section: Discussionsupporting
confidence: 92%
“…[18][19][20][21] Other medications utilized in the pediatric cardiac intensive care unit have also been noted to be incidentally associated with an increase in urine output and a lower risk of acute kidney injury, specifically, dexmedetomidine. 22 Aminophylline's effects on the kidneys are likely mediated by several mechanisms that are shared by all xanthine derivatives in a dose-dependent manner. Lower concentrations (2-3 µg/mL of theophylline equivalents) have been shown to result in adenosine receptor antagonism leading to inhibition of adenosine-related vasoconstriction of the afferent arterioles and improvement in renal blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…18 19 20 21 Other medications utilized in the pediatric cardiac intensive care unit have also been noted to be incidentally associated with an increase in urine output and a lower risk of acute kidney injury, specifically, dexmedetomidine. 22…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis by Loomba et al found reductions in AKI, length of stay, and mortality in patients exposed to dexmedetomidine. 16 The authors found an average bolus dose of 0.82 mg/ kg and an average infusion dose of 0.54 mg/kg/h. 16 In the 2 largest randomized, double-blind, placebo-controlled trials involving solely cardiac surgical patients, an infusion of dexmedetomidine at 0.4 mg/kg/h with no bolus was initiated after the induction of anesthesia and continued for 24 hours (in the study by Soh et al with 108 total patients) or continued for 24 hours after the end of surgery (in the study by Cho et al with 200 total patients).…”
mentioning
confidence: 97%
“…16 The authors found an average bolus dose of 0.82 mg/ kg and an average infusion dose of 0.54 mg/kg/h. 16 In the 2 largest randomized, double-blind, placebo-controlled trials involving solely cardiac surgical patients, an infusion of dexmedetomidine at 0.4 mg/kg/h with no bolus was initiated after the induction of anesthesia and continued for 24 hours (in the study by Soh et al with 108 total patients) or continued for 24 hours after the end of surgery (in the study by Cho et al with 200 total patients). 9,10 The authors of these studies noted no differences in bradycardia or hypotension between placebo and dexmedetomidine, suggesting that perhaps a dexmedetomidine dose of 0.4 mg/kg/h is a reasonable choice for the intervention arm of a larger trial.…”
mentioning
confidence: 97%